A case of lymphatic flow evaluation using indocyanine green fluorescence imaging for recurrence of anastomotic site after laparoscopic right hemicolectomy - Keita Sato; Yosuke Yamauchi; Koji Takahashi (Surgical Case Reports)
Abstract Background Anastomotic recurrence of colorectal cancer is rare, but reoperation improves prognosis. However, there is no clear evidence regarding the extent of dissection, and there are few reports on the details of surgery. We used intraoperative lymphatic flow imaging with indocyanine green (ICG) fluorescence as a reference to determine the range of additional resection. Case presentation The patient was a 75-year-old man who underwent laparoscopic right hemicolectomy and extracorporeal functional terminal anastomosis for ascending colon cancer 4 years ago. Histopathological examination revealed a well-differentiated tubular adenocarcinoma, T4aN0M0, pathological stageIIB. During follow-up, anemia was observed, and colonoscopy indicated anastomotic recurrence, so additional laparoscopic resection was performed. Intraoperatively, ICG was injected into the anastomotic site, and the operation proceeded under near-infrared light observation. Lymphatic vessels along the middle colonic artery were visualized down to the root of the vessel. Using this as an indicator, the vessel was ligated from the root. Using the fact that the lymphatic vessels were also depicted in the small intestinal mesentery on the oral side of the anastomosis as an indicator, the small intestine and mesentery were resected about 7 cm from the anastomosis. Conclusions The optimal surgical approach for anastomotic recurrence of colorectal cancer has not been defined. Intraoperative ICG fluorescence imaging can provide images of lymphatic flow from the site of recurrence and may be an indicator of lymph node dissection in the case of anastomotic recurrence.